Cover Feature: Capture of Gaseous Iodine in Isoreticular Zirconium‐Based UiO‐n Metal‐Organic Frameworks: Influence of Amino Functionalization, DFT Calculations, Raman and EPR Spectroscopic Investigation (Chem. Eur. J. 14/2022). Issue 14 (18th February 2022) - Leloire, Maeva; Walshe, Catherine; Devaux, Philippe; Giovine, Raynald; Duval, Sylvain; Bousquet, Till; Chibani, Siwar; Paul, Jean‐Francois; Moissette, Alain; Vezin, Hervé; Nerisson, Philippe; Cantrel, Laurent; et al.
Abstract : Gaseous iodine has been capture d by using a series of zirconium‐based UiO‐n metal–organic framework (MOF) sorbents. This study highlights the significant role of amino groups attached to the organic linker, which enhance the iodine uptake capacity, as well as its conversion into anionic iodide I3 − species, trapped within UiO‐n cavities. More information can be found in the Research Article by T. Loiseau et al. (DOI: 10.1002/chem.202104437 ). Margot Friscourt and Orfeas Plastiras are thanked for the cover artwork.